2021
DOI: 10.1007/s40266-021-00839-5
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Comparison of Three Anticholinergic Drug Scales in Older Adult Patients and Development of Postoperative Delirium: A Prospective Observational Study

Abstract: Background Postoperative delirium (POD) is a frequent and serious complication after surgery. Evidence of a relationship between anticholinergic medication and the development of delirium is inconclusive, but studies on POD are rare. Objectives The objective of this study was to evaluate the anticholinergic load of preoperative medication in older adult patients and its association with the development of POD. Methods This investigation was part of the European BioCog project (http://www.bioco g.eu), a prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
2
6
1
Order By: Relevance
“…Pasina et al also used the Anticholinergic Cognitive Burden Scale in their recently published study and did not find a clear association between anticholinergic burden and delirium in patients admitted to an acute geriatric ward (44). Also, in contrast to our findings, a recently published study by Heinrich et al found no association between preoperative anticholinergic load and POD using the Anticholinergic Cognitive Burden Scale, the Anticholinergic Drug Score and the ARS (24). However, compared to our study, these patients were significantly younger (POD: 74 years, no POD: 71 years in median) and patients with more than mild cognitive impairment (Mini-Mental State Examination score ≤ 23 points) were excluded.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Pasina et al also used the Anticholinergic Cognitive Burden Scale in their recently published study and did not find a clear association between anticholinergic burden and delirium in patients admitted to an acute geriatric ward (44). Also, in contrast to our findings, a recently published study by Heinrich et al found no association between preoperative anticholinergic load and POD using the Anticholinergic Cognitive Burden Scale, the Anticholinergic Drug Score and the ARS (24). However, compared to our study, these patients were significantly younger (POD: 74 years, no POD: 71 years in median) and patients with more than mild cognitive impairment (Mini-Mental State Examination score ≤ 23 points) were excluded.…”
Section: Discussioncontrasting
confidence: 99%
“…Anticholinergic burden has been associated with delirium in several settings (18,20,21), although results were conflicting (22). Studies on the effect of DAPs on POD are less frequent, and their results were also inconsistent, with one positive (23) and two negatives studies (24,25). Different results could be caused by the use of different scores calculating anticholinergic burden, small sample sizes, and different definitions of delirium.…”
Section: Introductionmentioning
confidence: 99%
“…Our ndings on the association between delirium and exposure to anticholinergics and sedatives are unique. One possible explanation for these ndings, as a neurotransmitter hypothesis, is the deterioration of cholinergic neurotransmission and expansion of neuroin ammation due to activation of microglial cells in patients with dementia [39,40]. Because of these pathological changes, patients may be more susceptible to the possible adverse effects of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Within the study, further publications with other questions have been published. Worth mentioning here seem the manuscripts, which investigate the association between preoperative medication use and development of POD and POCD [ 22 ] or between three Anticholinergic Drug Scales and development of POD [ 23 ] and between radiological, chemical and pharmacological cholinergic system parameters and preoperative neurocognitive disorder [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…POD was assessed daily through a validated delirium screening (using the Nursing Delirium Screening Scale, Confusion Assessment Method and a patient chart review) until the 7th postoperative day. For a detailed description of the assessment, please refer to previous publications [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%